JavaFX for dummies - Lowe, Doug 1959- (Laura Ann); 1906-1998.; 1970- (Hoboken, NJ. For Dummies, a Wiley brand, 2015)
Introduction -- Getting started with JavaFX -- JavaFX controls -- Enhancing your scenic design -- Making your programs come alive -- The part of tens.
"Learn to install the JavaFX development tools, including the JavaFX SDK, the Java SE JDK, and NetBeans. Develop desktop, mobile, and browser apps. Use HTML5 and CSS3 with JavaFX." Includes index.
Keywords: Java (Computer program language); Graphical user interfaces (Computer systems); Application software -- Development; Internet programming; JavaFX (Electronic resource); Application software; Java (Computer program language); Internet programming